STUDI PERBANDINGAN KINERJA GEDUNG MENGGUNAKAN BASE ISOLATOR TYPE HIGH DAMPING RUBBER BEARING (HDRB) 8 LANTAI DAN 25 LANTAI (Studi Kasus: Rumah Susun Politeknik Pekerjaan Umum) - Fasikhullisan, Fasikhullisan; Antonius, Antonius; Setiyawan, Prabowo (Politeknik Negeri Semarang, 2024)
In recent years a number of areas in the country have experienced earthquakes, resulting in deaths and damage to buildings. Indonesia is located in the Pacific Volcano Rim and is a country with the most active volcanoes in the world, so earthquakes often occur. In this thesis, a comparative analysis of the use of Base Isolators in an 8-storey building and a case study of Semarang Public Works Polytechnic Flats is conducted. The analysis uses ETABS V18 Software. The Vibration Period of the 8-Storey Building without Base Isolator in the X direction is 0.597s and when added Base Isolator becomes 2.099s Reduction of 58% while the Vibration Period of the 25-Storey Building without Base Isolator in the X direction is 2.65s and which has been given a Base Isolator of 2.902s Reduction of 8,7%. In conclusion, the higher the building, the smaller the Reduction Rate or the less useful the use of Base Isolator.